A Comparative Analysis of Government Systems: A Theoretical Study of Presidential, Parliamentary, and Indonesia’s Sui Generis Constitutional Dialectic Systems - Ogi Pracoyo; Reza Anggara Bahar; Yovan Iristian (Faculty of Law, University of Dr. Soetomo, 2026)
This research examines the complex dynamics of global governance models through a comparative lens, focusing on the fundamental dichotomy between presidential and parliamentary systems and the unique constitutional evolution of Indonesia. The primary objective is to analyze the structural efficacy, accountability mechanisms, and stability profiles of these systems in the context of contemporary democratic challenges such as the rise of populism and institutional erosion. Utilizing a normative juridical and comparative qualitative methodology, the study synthesizes constitutional provisions, recent Scopus-indexed literature (2020-2025), and landmark judicial decisions to provide an expert-level evaluation of institutional design. The findings reveal that while parliamentary systems excel in representativeness and collective responsibility through executive-legislative fusion, they often struggle with coalition instability. Conversely, presidential systems offer executive stability through fixed tenure but face risks of polarization, gridlock, and power concentration. Indonesia's system is identified as a